Study of gastrointestinal parasites in the iberian wolf (Canis lupus signatus) - Pereira, Ana Luísa de Oliveira (2018)
Iberian wolf (Canis lupus signatus), is the largest carnivore in Iberian Peninsula and is threatened with extinction. The aim of this study was to contribute to the knowledge of helminthic and protozoa fauna, in the wolf populations from the North of Spain, with the perspective to evaluate the health and surveillance of the diseases of these packs. One hundred and seventy seven samples of faeces of Canis lupus signatus, were collected from the environment in the North of Spain, between 2013 and 2014 and submitted to coprological methods. Helminth eggs were detected on 101 (57.0 %), and simple infections were more frequent with a prevalence of 53.4 % comparing with multiple infections. In the overall samples, eggs from Capillaria spp. (41.5 %) were the most frequently detected, followed by Toxocara spp. (40.5 %), Ancylostomatidae (29.7 %), Taeniidae (26.7 %) and Trichuris spp. (25.7 %). Results are discussed and compared with earlier published studies, especially to check the present status of helminthic infections in the wolf populations in that region. Additionally a subsample was analysed using a immunofluorescent assay (IFA) to identify the presence of Giardia spp. and Cryptosporidium spp. Fifty faecal samples were analysed, of which ten (20 %) were positive. Simple infections were more frequent, with seven (14 %) samples positive for Giardia spp. and two (4 %) positive for Cryptosporidium spp. Multiple infections with both protozoan species were found in just one (2 %) sample. Faecal samples, even frozen, revealed to be a valuable tool, to detect and identify helminthic and protozoa infections from wolves in the scope of surveillance programs.